2(-2x-12)+4=-2x-2x-20

Simple and best practice solution for 2(-2x-12)+4=-2x-2x-20 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(-2x-12)+4=-2x-2x-20 equation:



2(-2x-12)+4=-2x-2x-20
We move all terms to the left:
2(-2x-12)+4-(-2x-2x-20)=0
We add all the numbers together, and all the variables
2(-2x-12)-(-4x-20)+4=0
We multiply parentheses
-4x-(-4x-20)-24+4=0
We get rid of parentheses
-4x+4x+20-24+4=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0

See similar equations:

| 5x+18=6x+x | | t/2+2=3 | | -2×-3=y | | 2x(x-3)(2x+1)=0 | | 3(y-50)-36=16 | | 17+m=8(m-4 | | 11/2y-1=3 | | -40=-2a+8(4-2a | | 1/3(18-6x)=8-2 | | 8.5x=17 | | 1/3(x-1/3)=7/18-2/3x | | 20-4n=12 | | x+6=15;9 | | -5(z-75)=-85 | | 7^x^2=7^2x+3 | | 11=t/3+7 | | 2+1/3t=1/4t | | -1/3(x-1/3)=7/18-2/3x | | y/8=-50 | | 205=50+(15+8)w | | M3=6y | | 2/3(x-4)=1/2(2x-6) | | 21+3j=9-3j-2 | | 6+8(7x+14)=174 | | (y-2)^3=0 | | 3(x+15)+5=3x-14 | | 5-6x=-11 | | -2+1/3(v+9)=1/2(6+2/3v | | F(r)=3.14r^2 | | 7(c+4)+(-4)=52 | | 6m-12=6+9m-24 | | 0.6666x+5=11 |

Equations solver categories